COMPETITIONS, RECREATIONAL COMPETITIONS AND EVENTS IN WINTER SPORTS AS A SOLUTION FOR THE POSITIVE DEVELOPMENT OF THE TOURIST DESTINATION OF SARAJEVO CANTON - Amer Hodžić, (Sport Scientific And Practical Aspects, 2025)
The aim of this paper is to determine and evaluate the current situation and possibilities of the offer of sports and recreational tourism in the Sarajevo Canton and to make some recommendations for its future development. More developed sports tourism in Sarajevo Canton would be a solution to reduce the extreme seasonality of tourism in Sarajevo Canton. Sports and recreational tourism would adequately contribute to the development of the tourist destination and the reduction of unemployment. This review article is based on the analysis of collected statistical and other relevant information and data through available websites and published statistical reports of Sarajevo Canton as well as published theoretical papers on the development of sports and recreational tourism, sports tourism, sports and recreational activities in affirmation and promotion of tourist destinations. Sarajevo Canton is today an attractive tourist destination. Enriching and expanding the offer in the field of sports tourism, Sarajevo Canton would become a very attractive tourist destination, with a constant increase in the number of tourist arrivals within the same with the effect of extending the average length of stay and increasing arrivals during the year when the lowest occupancy in November, December, January and February Additional information was gathered through research through available information and field research to the extent that was available and necessary. All collected data were analyzed through comparison criteria